Diazadithia[7]helicenes: Synthetic Exploration, Solid‐State Structure, and Properties. Issue 36 (22nd July 2013) - Waghray, Deepali; Cloet, Arvid; Van Hecke, Kristof; Mertens, Stijn F. L.; De Feyter, Steven; Van Meervelt, Luc; Van der Auweraer, Mark; Dehaen, Wim
Abstract Diazadithia[7]helicenes were synthesized from the readily available building block ethyl 7‐chloro‐8‐formylthieno[3, 2‐f]quinoline‐2‐carboxylate by a Wittig reaction–photocyclization strategy. The helicene core was functionalized by nucleophilic aromatic substitution with a variety of nucleophiles (e.g., O‐, N‐, and C‐centered) and palladium‐catalyzed reactions such as Suzuki coupling and Buchwald–Hartwig amination. Racemization studies confirmed that the enantiopure forms of these [7]helicenes are conformationally stable compared to their lower analogues. The solid‐state structures of the novel diazadithia[7]helicenes were determined by single‐crystal X‐ray diffraction. The crystal structures of these azathia[7]helicenes show columnar stacking in antiparallel fashion. The HOMO–LUMO gaps of the new compounds were determined on the basis of electrochemical and optical measurements.